Optimasi Penggunaan Pupuk Manure Sapi dan Urea Dosis Berbeda Untuk Produksi Bibit Stek Rumput Pakchong (Pennisetum glaucum) di Lampung Selatan: Optimization of the Use of Cow Manure and Urea Fertilizer in Different Doses for the Production of Pakchong Grass (Pennisetum glaucum) Cuttings in South Lampung - Sentosa, Akmal; karti, panca dewi manu hara; Prihantoro, Iwan (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
This study aims to measure the effect of different doses of cow manure and urea fertilizer on plant growth and the production quality of Pakchong grass cuttings. A factorial Randomized Block Design (RBD) (3 doses of cow manure and 3 doses of urea) was used with 3 replications. The first factor was the dose of cow feces (0-, 5-, and 10-tons ha-1), while the second factor was the dose of urea (100, 200, and 300 kg ha-1). The results showed that there was no interaction between cow manure and urea fertilizer on plant height, stem diameter, total leaves, number of tillers, number of tillers ready for harvest, and production of Pakchong grass cuttings. However, each factor significantly affected (p<0.05) the growth and cutting production of Pakchong grass. The use of cow manure fertilizer at a dose of 10 tons ha-1 and urea fertilizer at a dose of 300 kg ha-1 provided optimum results in increasing plant growth and the production of Pakchong grass cuttings. Key words: cow manure, cuttings production, morphology, pakchong grass, urea fertilizer